Health-related quality of life in different trimesters during pregnancy - Wu, Huailiang; Sun, Weiwei; Chen, Hanqing; Wu, Yanxin; Ding, Wenjing; Liang, Shangqiang; Huang, Xinyu; Chen, Haitian; Zeng, Qing; Li, Zhuyu; Xiong, Peng; Huang, Jian; et al. (Health and quality of life outcomes, 2021)
Pregnant women experience physical, physiological, and mental changes. Health-related quality of life (HRQoL) is a relevant indicator of psychological and physical behaviours, changing over the course of pregnancy. This study aims to assess HRQoL of pregnant women during different stages of pregnancy. This cross-sectional study was performed using the The EuroQoL Group's five-dimension five-level questionnaire (EQ-5D-5L) to assess the HRQoL of pregnant women, and demographic data were collected. This study was conducted in a regional university hospital in Guangzhou, China. A total of 908 pregnant women were included in this study. Pregnant women in the early 2.sup.nd trimester had the highest HRQoL. The HRQoL of pregnant women rose from the 1st trimester to the early 2nd trimester, and dropped to the bottom at the late 3rd trimester due to some physical and mental changes. Reports of pain/discomfort problem were the most common (46.0%) while self-care were the least concern. More than 10% of pregnant women in the 1st trimester had health-related problems in at least one dimension of whole five dimensions. In the whole sample, the EuroQoL Group's visual analog scale (EQ-VAS) was 87.86 [+ or -] 9.16. Across the gestational stages, the HRQoL remained stable during the pregnancy but the highest value was observed in the 1st trimester (89.65 [+ or -] 10.13) while the lowest was in the late 3rd trimester (87.28 [+ or -] 9.13). During pregnancy, HRQoL were associated with gestational trimesters in a certain degree. HRQoL was the highest in the early 2nd trimester and then decreased to the lowest in the late 3rd trimester due to a series of physical and psychological changes. Therefore, obstetric doctors and medical institutions should give more attention and care to pregnant women in the late 3rd trimester.